Does open reduction internal fixation using a volar locking plate and closed reduction percutaneous pinning using K wires provide similar functional and radiological outcomes for unstable distal radius fractures? - Radaideh Ahmad; Abualadas Jehad; Anaqreh Yazan; Alnemer Adham; Alghzawi Ahmad Abdalmajeed; Abualadas Rawan; Alawneh Mohammad; Essa Suhaib Bani (SICOT-J, 2023)
Background: Distal radius fractures (DRFs) are a common orthopedic injury, with open reduction internal fixation (ORIF) and closed reduction percutaneous pinning (CRPP) being the two most frequently used methods for treating unstable DRFs. The optimal treatment approach for DRFs is still a matter of debate. Therefore, this retrospective analysis aimed to compare the functional and radiological outcomes of ORIF and CRPP to determine the most effective approach for treating unstable DRFs. Material and Methods: A total of 89 patients were included in this retrospective study; 34 underwent CRPP and 55 underwent ORIF (61 males and 28 females, mean age: 35.5). Radiographic measurements of radial inclination, radial height, and volar tilt, as well as patient-rated wrist evaluation (PRWE) scores for pain and function, were used to evaluate the functional and radiological outcomes during the final follow-up period, ranging from 1 to 4 years. Results: There were significant improvements in the radiographic measurements for both groups, indicating a good reduction. However, the two fixation methods had no significant difference in radiographic measurements during the entire follow-up period. Regarding PRWE scores, there was a significant difference between the two groups, with patients in the CRPP group reporting better wrist function and less pain. Conclusions: Both CRPP and ORIF are effective methods for treating unstable DRFs. Achieving an acceptable reduction did not correlate with better pain management, function, or the ability to carry out day-to-day activities. However, patients treated with CRPP had better wrist function and less pain during follow-up. Radiographic measurements did not differ significantly between the two groups. Clinicians should consider closed-reduction percutaneous pinning as a viable and effective treatment option for distal radius fractures, particularly when optimal wrist function and pain management are important considerations.